2013
DOI: 10.4028/www.scientific.net/amr.706-708.24
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antioxidant Chitosan Film Incorporated with Pomegranate Peel Extract

Abstract: A novel antioxidant chitosan film incorporated with pomegranate peel extract (PPE) (0, 1%, 2%, and 3% (w/v)) was developed. The mechanical property, water vapor permeability, total phenolic content and antioxidant activity of the films were investigated. Fourier transform infrared (FTIR) spectra revealed that good interactions occurred between functional groups of chitosan with PPE. The flexibility and water vapor barrier property were improved by incorporation with PPE. Films containing PPE had higher total p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Other studies have reported that pomegranate peel extract enhanced the antioxidant capacity of chitosan-based edible films [40]. Similar data were reported by Yuan et al [41], Yuan et al [42], Kannat et al [79], and Fan et al [98], who found that the incorporation of pomegranate peel extract improved the antioxidant activity of chitosan-and PVA-based films.…”
Section: Antioxidant Activity (Dpph) Of Edible Filmsupporting
confidence: 76%
See 1 more Smart Citation
“…Other studies have reported that pomegranate peel extract enhanced the antioxidant capacity of chitosan-based edible films [40]. Similar data were reported by Yuan et al [41], Yuan et al [42], Kannat et al [79], and Fan et al [98], who found that the incorporation of pomegranate peel extract improved the antioxidant activity of chitosan-and PVA-based films.…”
Section: Antioxidant Activity (Dpph) Of Edible Filmsupporting
confidence: 76%
“…These results are in a good agreement with previous studies by Qin et al [40] and Mabrouk et al [97], who reported that the addition of pomegranate peel extract increased the phenolic activity of chitosan-and pectin-based films. In this context, Fan et al [98] showed a 13-fold increase in the phenolic activity (from 3.21 ± 0.12 to 43.07 ± 0.07 mg/g) of a chitosan-based film with the incorporation of 3% pomegranate peel extract.…”
Section: Phenolic Content and Antioxidant And Antimicrobial Activity ...mentioning
confidence: 99%
“…A significant increase in TPC of chitosan‐based films was also observed due to the incorporation of pomegranate peel extract (Fan et al., 2013). Other researchers have also reported a remarkable increase in the TPC of biopolymer‐based films due to the incorporation of PPP and pomegranate peel extract (Kumar et al., 2021).…”
Section: Resultsmentioning
confidence: 97%
“…Eleven known compounds were identified to be crepidatin 4 [24], moscatilin 5 [25], 4,5,4′-trihydroxy-3,3′-dimethoxybibenzyl 6 [26], 4′,5-dihydroxy-3,3′-dimethoxybibenzyl 7 [27], tristin 8 [28], batatasin III 9 [27], 3,5,3′-hydroxybibenzyl 10 [29], aphyllals C 11 [15], densiflorol A 12 [30], dihydroconiferyl dihydro- p -coumarate 13 [31], p -hydroxyphenethyl trans -ferulate 14 [32] by spectroscopic analysis and comparing their spectral data with literature.…”
Section: Resultsmentioning
confidence: 99%